Evaluation of Analgesic Activity Corypalmine and Panasenoside Compounds on Cox-2 Receptors In-Silico - Lesbatta, Kezia Josawel; Watuguly, Theopilus Wilhelmus; Kakisina, Alter Glen; Anggraeni, Andi Sri Dewi (Universitas Pattimura, 2025)
Pain is a mechanism that occurs due to stimulation of nociceptors as pain receptors that cause ongoing or future tissue damage. Analgesic drugs that are usually used are COX-2 inhibitor drugs that can inhibit the activity of the COX-2 enzyme in synthesizing Prostaglandins (PG) which respond to pain and inflammation. Specific research on active compounds such as corypalmine and panasenoside related to their effects as analgesics has not been widely carried out, so it is necessary to predict the effects of both compounds by analyzing their activity on the COX-2 protein through in silico docking studies. This study aims to see the analgesic activity between the two compounds as COX-2 inhibitors. Testing was carried out through the stages of protein and ligand preparation, method validation, molecular docking of corypalmine and panasenoside compounds with COX-2 and visualization of bonds using Ligplot+. The results showed that the corypalmine docking score was more negative than panasenoside on COX-2, respectively -60.33 and -42.02. It can be concluded that the corypalmine compound is able to bind more strongly to COOX-2 and predicted to have a strong and more stable analgesic effect than panacea.